Penerapan Media Pop-Up Book Matematika untuk Meningkatkan Pemahaman Konsep Bangun Datar Siswa Sekolah Dasar: The Implementation of Mathematics Pop-Up Book Media to Enhance Elementary School Students' Understanding of 2D Shape Concepts - Salma Salma; Luthfi Hamdani Maula; Arsyi Rizqia Amalia (ITScience (Information Technology and Science), 2026)
Conceptual understanding is a fundamental skill that students must possess in mathematics learning. However, preliminary observations in the fifth-grade class at SDN Sukasirna indicated that students' understanding of 2D shapes—specifically regarding the area of these shapes—was low. This situation was evidenced by poor learning outcomes, with a class average score of 58 and no students meeting the Minimum Mastery Criteria (KKM). This lack of conceptual understanding was attributed to teacher-centered instruction and a lack of variety in the learning media used. This study aimed to describe the implementation of the PUBMATIKA (Mathematics Pop-Up Book) medium and to analyze the improvement in fifth-grade students' understanding of 2D shape concepts. The study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted over two cycles. The subjects were 10 fifth-grade students at SDN Sukasirna. Data collection techniques included tests, observations, interviews, and documentation. Data were analyzed using both quantitative and qualitative descriptive methods. The results showed that the implementation of the PUBMATIKA medium improved students' understanding of 2D shape concepts. The percentage of students achieving mastery increased from 30% in the pre-cycle stage to 50% in Cycle I, and further rose to 80% in Cycle II. Thus, the PUBMATIKA medium is effective for enhancing elementary students' understanding of 2D shape concepts, particularly regarding the area of such shapes.